A case of catamenial erythema multiforme major successfully treated with goserelin - Tyack, Lauren T; Stuckey, Bronwyn G A; Walsh, John P (Endocrinology, diabetes & metabolism case reports, 2023)
We report a case of catamenial erythema multiforme major in a 46-year-old female. She was treated successfully with goserelin, a GnRH agonist, until the expected age of menopause; however, its therapeutic effects persisted for longer than expected, possibly due to accumulation in adipose tissue. A group of menstrual cycle-related dermatoses and hypersensitivity syndromes exist but are rarely reported in the literature. A history of recurrent cutaneous eruptions in premenopausal females should be considered in the context of the menstrual cycle. The diagnosis of menstrual cycle-related dermatoses is largely clinical, although provocation testing can assist. Treatment options are broad and are aimed at reducing the immune response and/or suppressing ovulation. Goserelin may accumulate and have a gonadotrophin-suppressing effect for longer than expected.